2007
DOI: 10.1111/j.1600-0609.2007.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

First clinical experience with simvastatin to overcome drug resistance in refractory multiple myeloma

Abstract: In vitro statins overcome cell adhesion-mediated drug resistance at non-toxic concentrations that are achievable in humans by standard dose simvastatin. A pilot phase-II trial was initiated to determine feasibility and antimyeloma efficacy. In six myeloma patients refractory to two cycles of bortezomib or bendamustine simvastatin was concomitantly administered during further two cycles. The therapy was well tolerated without grade 3/4 toxicity. Intrapatient (cycles I/II vs. III/IV) and interpatient comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 8 publications
1
38
0
Order By: Relevance
“…Several studies have reported that statins inhibits proliferation and cell division of cancer cells (44,45), and clinical trials have shown that the addition of statins to traditional chemotherapeutic strategies can increase the efficacy of chemotherapy (46,47). In particular, Martirosyan and colleagues (36) recently showed that lovastatin induces apoptosis of ovarian cancer cells and synergizes with doxorubicin, which is used in the treatment of primary and relapsed drug-resistant ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that statins inhibits proliferation and cell division of cancer cells (44,45), and clinical trials have shown that the addition of statins to traditional chemotherapeutic strategies can increase the efficacy of chemotherapy (46,47). In particular, Martirosyan and colleagues (36) recently showed that lovastatin induces apoptosis of ovarian cancer cells and synergizes with doxorubicin, which is used in the treatment of primary and relapsed drug-resistant ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The former may have some applicability to bortezomib as P-glycoprotein blockade enhanced bortezomib sensitivity in models of leukemia (113) and Ewing's sarcoma (114). Another approach to overcome acquired resistance may be to block 3-hydroxy-3-methyl-glutaryl-CoA reductase (115), although the mechanism involved has not been defined. Further studies will be needed with in vitro preclinical models of bortezomib resistance, ideally validated with clinical samples from patients with acquired resistance, to better delineate the relevant mechanisms in vivo and test targeted approaches to abrogate these pathways.…”
Section: Resistance To Proteasome Inhibitorsmentioning
confidence: 99%
“…Statins exert antiproliferative, pro-apoptotic and anti-invasive effects in different cancer cell lines with varying sensitivity. The antimyeloma activity of statins in humans was first reported with the concomitant simvastatin administration in refractory multiple myeloma (MM), which showed reduced drug resistance (18). However, high-dose simvastatin treatment (15 mg/kg/day) in heavily pretreated MM patients transiently increased osteoclast activity and gastrointestinal side-effects, leading to premature discontinuation (19).…”
Section: Antitumor Effects Of Statins In Preclinical Studiesmentioning
confidence: 99%